2021
DOI: 10.3390/md19100551
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Scaffold for Mineralized Tissues Regeneration

Abstract: Conventional bone grafting procedures used to treat bone defects have several limitations. An important aspect of bone tissue engineering is developing novel bone substitute biomaterials for bone grafts to repair orthopedic defects. Considerable attention has been given to chitosan, a natural biopolymer primarily extracted from crustacean shells, which offers desirable characteristics, such as being biocompatible, biodegradable, and osteoconductive. This review presents an overview of the chitosan-based biomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 72 publications
2
53
0
Order By: Relevance
“…It has the ability to stimulate the recruitment and adhesion of osteogenic progenitor cells, facilitating bone formation. In addition, it has been shown that no inflammatory or allergic reactions occur after topical application ( Kim et al, 2003 ; Waibel et al, 2011 ; Azuma et al, 2015 ; Sukpaita et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has the ability to stimulate the recruitment and adhesion of osteogenic progenitor cells, facilitating bone formation. In addition, it has been shown that no inflammatory or allergic reactions occur after topical application ( Kim et al, 2003 ; Waibel et al, 2011 ; Azuma et al, 2015 ; Sukpaita et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has been formulated in different systems for bone tissue engineering, including scaffolds, sponges, hydrogels, micro-nanospheres, and membranes, among others [98,102]. According to Sukpaita et al, 3D biomaterial scaffolds are one of the three main pillars of bone tissue engineering, along with osteogenic stem cells and bioactive molecules such as growth factors or drugs.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Synthetic polymers such as polylactic acid (PLA) [4], polyvinyl alcohol (PVA) [5], poly (lactic-co-glycolic) (PLGA) [6], and poly ε-caprolactone (PCL) [7] have been used for the preparation of 3D scaffolds due to their easily adjustable porosity, mechanical performance, and degradation time. With their higher biocompatibility, natural polymers such as gelatin [8], collagen [9], chitosan [10], alginate [11], elastin [12], and fibrin [13] have attracted researchers' attention for the preparation of 3D scaffolds that faithfully replicate the native tissue vasculature and channel interconnections that allow the perfusion of nutrients and oxygen diffusion during regeneration. Moreover, the degradation kinetics can be coordinated with the regenerative effects in order to drive the reformation of scarless tissue, reducing the necessity for secondary surgical procedures to eradicate any degenerated scaffold [14].…”
Section: Introductionmentioning
confidence: 99%